The Effect of The Quantum Learning Model on Student Learning Outcomes - Pribadi Arif; Jaryono Jaryono; Lina Rifda Naufalin; Herman Sambodo (Universitas Negeri Semarang, 2023)
This research aims to analyze the effect of the Quantum Learning model on student learning outcomes in economics subjects. This research was motivated by the many students in class XI IPS at SMA Negeri 3 Purwokerto who obtained daily test scores below the Minimum Completeness Criteria (KKM) in economics subjects. The research method used is a Quasi-Experimental Design that uses an experimental and control class. This study's population was all class XI IPS students at SMA Negeri 3 Purwokerto. The number of samples in this study was 71 respondents who were students of class XI IPS 3 and 4. The sampling technique used was the purposive sampling technique. Based on the data analysis that has been done, the Quantum Learning Model has a positive effect on student learning outcomes in economics class XI IPS at SMA Negeri 3 Purwokerto. The implication of the conclusions above is that teachers and schools are advised to optimize learning by creating comfort, fun, and opportunities for students to be active in learning. The efforts that can be made are applying the Quantum Learning model because the Quantum Learning model has been proven to be able to improve student learning outcomes.